Analisis Strategi Pemasaran Segment Government PT. Telkom Indonesia Witel Yogyakarta Dalam Meningkatkan Jumlah Penjualan - Lisa Listiyani; Anas Hidayat (Ebisnis Manajemen, 2023)
PT. Telkom Indonesia Tbk is an Indonesian state-owned company that operates in the fields of information technology, communications and telecommunications networks. This company has several important divisions or segments in carrying out business strategies, one of which is the government segment. The government segment cannot do hard selling like other segments. This is because the government segment is included in B2B sales and cannot expand the market easily. Apart from that, because government segment customers are government agencies, the government's budget is also limited because it is regulated in the APBN. Regarding the problems and challenges faced by government services, the author wants to analyze the government segment's business strategy in increasing sales with customers and limited government budgets. The final internship assignment was prepared by the author using qualitative methods. Data collection was carried out by conducting interviews with account managers and supervisors. The results of interviews and observations of the government segment have strategies in conducting B2B sales, namely carrying out acquisitions or scaling, conducting account manager soft skills training, building and maintaining customer loyalty, conducting outreach related to the success of work programs that have been implemented by other regions, conducting outreach and offering programs work, holding a service business request (SBR) program, carrying out business processes with direct selling and personal selling, having an account manager's role as a consultant, building and maintaining customer trust, and registering various Telkom products in the E-Catalog.